Representasi Kehamilan Remaja Di Luar Nikah Film Dua Garis Biru (Analisis Semiotika Roland Barthes) - Safria Safria; Syukri; Wardah (Universitas Muhammadiyah Kotabumi, 2026)
The film Dua Garis Biru represents the phenomenon of teenage pregnancy outside of marriage as a complex social issue with significant meaning. This research aims to analyze the representation of teenage pregnancy in the film Dua Garis Biru by revealing the meanings of denotation, connotation, and myth constructed through visual and audio-visual signs within the film. This research employs a qualitative approach using Roland Barthes’ semiotic analysis method. The data were obtained through direct observation of scenes in the film, supported by documentation and interpretative analysis. The findings show that the film portrays teenage pregnancy as an event filled with moral pressure, social control, and the dominance of adult roles in determining solutions. The results indicate that adolescents have limited choices because decisions are predominantly made by parents and social institutions. Furthermore, the myths presented in the film normalize the view that teenage pregnancy is a social deviation that must be resolved through compliance with cultural norms and collective moral values. Therefore, Dua Garis Biru functions not only as entertainment media but also as a means of producing and reproducing social ideology concerning morality, responsibility, gender roles, and the influence of family in regulating teenage life. This study contributes to the field of communication by illustrating how media reinforces societal norms regarding juvenile issues.